Interlayer Chemistry of Layered Electrode Materials in Energy Storage Devices - Zhang, Yufei; Ang, Edison Huixiang; Yang, Yang; Ye, Minghui; Du, Wencheng; Li, Cheng Chao (Advanced functional materials, 2021)
With the constant focus on energy storage devices, layered materials are ideal electrodes for the new generation of highly efficient secondary ion batteries and supercapacitors due to their flexible 2D structures and high theoretical capacities. However, the small interlayer distances in layered electrode materials and the strong Columbic interactions between the working ions and host lattice anions cause slow ion diffusion. In addition, structural collapse during repeated ion insertion and extraction reduces the cycling lifetime. As such, interlayer engineering strategies are effective approaches to optimize ion transmission kinetics and structural integrity. In view of the latest research on the interlayer engineering of layered materials, this review will discuss useful strategies to improve electrode performance. The synthetic strategies, characterization techniques, and effects of interlayer‐engineered layered materials, including metal oxides, metal sulfides, carbonous materials, and MXenes, are discussed in detail. The future outlook and challenges for interlayer engineering are also presented, which may pave the way for the development of new layered materials. Interlayer engineering has emerged as a powerful approach for tailoring layered electrodes with flexible structures, tunable properties, and multiple active sites for secondary batteries and supercapacitors. This review highlights various tactics for interlayer engineering and explores their induced effects on electrochemical performance. Finally, the challenges and outlook for future work are also presented.